Answer:
Explanation:Answer:
Reorder the terms:
8 + 6p + -4p = 3(p + 4)
Combine like terms: 6p + -4p = 2p
8 + 2p = 3(p + 4)
Reorder the terms:
8 + 2p = 3(4 + p)
8 + 2p = (4 * 3 + p * 3)
8 + 2p = (12 + 3p)
Solving
8 + 2p = 12 + 3p
Solving for variable 'p'.
Move all terms containing p to the left, all other terms to the right.
Add '-3p' to each side of the equation.
8 + 2p + -3p = 12 + 3p + -3p
Combine like terms: 2p + -3p = -1p
8 + -1p = 12 + 3p + -3p
Combine like terms: 3p + -3p = 0
8 + -1p = 12 + 0
8 + -1p = 12
Add '-8' to each side of the equation.
8 + -8 + -1p = 12 + -8
Combine like terms: 8 + -8 = 0
0 + -1p = 12 + -8
-1p = 12 + -8
Comb
![\lim_(n \to \infty) a_n \lim_(n \to \infty) a_n](https://img.qammunity.org/2020/formulas/biology/middle-school/s1oavzz46zrati0qobc0jb7kv0fkj9rqvi.png)